Toxoplasmosis Epidemiology, Prevention and Control - Hotea, Ionela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Scientific motivation to publish this book comes from the increased interest in the study of toxoplasmosis, showed all over the world. Though the Toxoplasma gondii infection was first discovered in 1908, toxoplasmosis remains a today's research topic, a realm of questions and dilemmas that interest both the veterinarians and the human doctors. Studies in the field are directed to the epidemiology of the disease, the sources of infection, epidemiological chains, being underlined the important feature in the transmission of this parasite: the ability to pass from one intermediate host to another intermediate host without passing through the final host - felids. An increased prevalence of toxoplasmosis in humans and animals, as well as the difficulty of coproscopic diagnosis of toxoplasmosis in cats, expensive serological examinations in both animals and humans, lack of diagnostic methods accessible to veterinarians in slaughterhouses, cultural and culinary differences of human patients, which can influence the prevalence of the disease, motivate the scientific and practical importance of the proposed book and reveal the importance of this topic for animal and human health. So, the proposed book will contain informations regarding the etiology and history of Toxoplasma gondii infection and also the parasite's morphology and biology. This work will contain a very detailed epidemiology of the toxoplasmosis from all over the world and for all species of animals. This chapter will include also personal findings of the authors about the Toxoplasma gondii seroprevalence in domestic animals from Romania. In the last part of the book we will present the main methods for toxoplasma diagnosis. At the end of the book we will synthesize the main routes for T. gondii infection and the recommendations for reducing toxoplasmosis seroprevalence.